Vissungo: o cantar banto nas Américas - Andréa Albuquerque Adour da Camara (2013)
This study is an investigation of four different documents, on which we seek to distinguish, both in Brazil and the United States, the richness of musical elements related to a Bantu heritage, presentified by the enslaved Africans brought to the Americas and their descendants. We have therefore selected two Brazilian documents: ‘O Negro e o Garimpo em Minas Gerais’, written by Aires da Mata Machado Filho and published in 1943; and the recordings made in Minas Gerais, in 1944, by Luiz Heitor Corrêa de Azevedo, a professor at ‘Escola Nacional de Música’, in collaboration with musicologist Alan Lomax from the American Folklife Center at the Library of Congress. We have equally selected two North-American documents: “Slave Songs of the United States: The Classic 1867 anthology”, compiled by William Francis Allen et al; and the recordings of songs from the South of the United States, made by Alan Lomax for the Library of Congress, beginning in 1933, and compliled at the CD “Negro Work Songs and Calls”. These documents share the fact of being the first written and phonographic records of chants of African origins in the Americas. The work of Aires da Mata Machado Filho presents the musical notation of the songs collected in the year of 1928, in the regions of São João da Chapada and Quartel do Indaiá, districts of Diamantina, Minas Gerais. According to him, these songs, called vissungos, were chanted in the language of Benguela. The word vissungo itself has Bantu origins, being etymologically translated as singing. The phonograms, recorded in the same field, in 1944, by Luiz Heitor Corrêa de Azevedo, help us perceive the limitations of models for registering music when in comparison with the production of singers belonging to this culture. These limitations are also seen when comparing the document recorded by Alan Lomax and the work of William Allen. The most important consideration from this study is that singing is the essence here, and, through the voice, the singers constitute a continuous temporality, uniting the past, present and future by the memory of ancestrality. By searching for contours, the registers neither indicate the importance of pause, absence, silence, nor do they translate the voice and its ways of use. These are elements that cannot be neglected since they convey sense. As a song, vissungos make voices and silence present, thus rebuilding the past and projecting itself as education (ex-ducere), edificating its tradition in the Americas.